Diplomasi Publik Baru Jakarta International Java Jazz Festival 2020 dalam Mempromosikan Brand Kota “Enjoy Jakarta” - Annaya Rania Nariswari (Jurnal Hubungan Internasional, 2021)
The state and non-state actors are competing with each other to make theregion as a destination for local and foreign tourists. Efforts to achieve this arecarried out through various international activities, including culture event. Thestudy aims to describe the practice of new public diplomacy through JakartaInternational Java Jazz Festival 2020, organized by PT Java FestivalProduction, in promoting “Enjoy Jakarta” city brand. This new publicdiplomacy practice is analyzed through qualitative research methods throughliterature studies by using Nicholas J. Cull’s theory of new public diplomacy.The festival is analyzed by dividing the event period into two stages,pre-event and main event. The results showed that the public got the impressionof city brand’s promotion as a tourist destination during the pre-event andmain event. The collaboration with the government also made it easier for theorganizer to achieve the purpose of the festival as a means of promotingJakarta tourism to a wider foreign public.